Asymptotic Estimation of the Eigenvalues and Eigenfunctions for the Sixth Order Boundary Value Problems - Qadr, Khelan. H.; Jwamer, Karwan H. F. (Sulaimani Journal for Pure and Applied Sciences, 2018)
This paper addresses an eigenvalue problem generated by sixth order differential equations with suitable boundary conditions, which contain a spectral parameter. The asymptotic expressions for sixth order linearly independent solutions as well as new asymptotic formulas for the eigenvalues with eigenfunctions of the boundary value problem are obtained.
Keywords: Eigenvalue problem; eigenfunction; spectral parameter; asymptotic formula